Investigation of Acetoin Biosynthesis by Bacillus subtilis ACA-DC 1176 Growing on Crude Glycerol in Flask and Bioreactor Trials - Dimitris Karayannis; Eleni Moraiti; Ourania Kalantzi; Seraphim Papanikolaou (Reactions)
Acetoin biosynthesis by two Bacillus subtilis strains valorising crude glycerol was thoroughly explored within a pre-defined range of culture conditions and systems. B. subtilis ACA-DC 1176 stood out for its higher efficiency in acetoin production, prompting an investigation into the potential for enhanced productivity through the evaluation of diverse culture conditions and media compositions. The primary by-products of the biodiesel and corn industries, namely crude glycerol and corn steep liquor, respectively, were successfully employed as the principal carbon and nitrogen sources of the newly developed low-cost culture medium. Furthermore, the results of the various feeding strategies that were tested indicated that the conversion of 2,3-butanediol (BDO) to acetoin occurred exclusively when the concentration of glycerol was below approximately 5 g/L. This seemed to be necessary for the production of NADH, which is essential for maintaining cellular processes. Following the complete depletion of glycerol, acetic acid increased and became the predominant metabolite, while both acetoin and BDO decreased, presumably resulting in ATP generation. This is likely a mechanism employed by the cell to generate energy in the absence of a carbon source. In the fed-batch bioreactor culture, the kinetics of metabolites differed, as there was no conversion of BDO to acetoin at the final depletion of glycerol. At volumetric mass transfer coefficient (kLa) levels exceeding approximately 70 1/h, the production of acetoin was favoured over that of BDO, with the highest observed acetoin/BDO ratio reaching 4.29 g/g. Conversely, at kLa values below approximately 60 1/h, the titres of acetoin and BDO were found to be nearly equal. The final concentrations of acetoin and BDO reached 36.0 g/L and 25.5 g/L, respectively, resulting in a total yield of both (acetoin + BDO) per glycerol consumption of 0.40 g/g. To the best of our knowledge, this is the first study to focus on acetoin production from crude glycerol fermentative valorisation. The study presents new findings regarding the parameters influencing the level of BDO conversion to acetoin. However, further research is required in order to gain a comprehensive understanding of the underlying phenomena and metabolic pathways involved.